2020
DOI: 10.1016/j.joen.2020.06.030
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Microbial and Antimicrobial Considerations in Regenerative Endodontic Therapy

Abstract: Introduction: Regenerative endodontic therapy (RET) has gained considerable attention and wide approval. Although it is being performed routinely, the outcomes remain unpredictable, and the optimal approaches for treatment are not established. It has been shown that bacterial persistence in root canals in these cases significantly interferes with healing and root maturation. However, few objective clinical studies have evaluated the complex microflora present in the infections or the efficacy of various clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 83 publications
(91 reference statements)
0
21
0
Order By: Relevance
“…The treatment of necrotic permanent immature tooth constitutes a challenge in endodontics since anatomic variation, caries, trauma, incomplete root development and other such harmful stimuli can arrest tooth development 1,3,9 . Pulp necrosis of an immature permanent tooth leads to discontinuation of tooth development causing thin dentinal walls and open apices.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The treatment of necrotic permanent immature tooth constitutes a challenge in endodontics since anatomic variation, caries, trauma, incomplete root development and other such harmful stimuli can arrest tooth development 1,3,9 . Pulp necrosis of an immature permanent tooth leads to discontinuation of tooth development causing thin dentinal walls and open apices.…”
Section: Discussionmentioning
confidence: 99%
“…The development of permanent immature teeth may be halted owing to various harmful stimuli such as caries, trauma, anatomic variations which leads to thin and fragile dentinal walls. The long-term survival of these teeth is conceded due to open apices, large apical diameters and short roots 1,2 . Conventional techniques of root canal filling rely on the presence of an apical constriction at the apex of the tooth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretically, if we can sterilize the canal, and recreate a 3D “biological filling” in the form of regenerated vital tissues this would ensure an optimum outcome. Regenerative strategies targeting mature teeth will most likely differ from those for immature permanent teeth, due to the different challenges encountered in both situations regarding the weak natural architecture of immature teeth, in addition to, the complexity of biofilms, toxins, and antigens which could reside in the larger dentinal tubules in these teeth ( He et al, 2017 ; Verma et al, 2017 ; Almutairi et al, 2019 ; Fouad, 2020 ). Excessive removal of tooth structure accompanying a TEC especially at pulp chamber walls and around the canal orifices, may decrease the tooth resistance to fracture during function.…”
Section: Regenerative and Minimally Invasive Endodontic Procedures: T...mentioning
confidence: 99%
“…A plethora of challenges lie ahead for REPs for favorable clinical and histological outcomes to be achieved in the future. It has been shown that residual bacteria in the root canal adversely affect wound healing and root maturation [ 19 , 201 , 202 ]. Microbial control of necrotic immature teeth with apical periodontitis is challenging; bacterial biofilms that adhere to the uneven surface of the blunderbuss canals render conventional debridement and disinfection exorbitantly difficult in root canal systems [ 19 , 201 , 202 ].…”
Section: Challenges and Future Prospects For The Application Of Bioma...mentioning
confidence: 99%